Analisis Penggunaan Aplikasi Google Drive Sebagai Media Penyimpanan Data - Safitri, Kenanga; Nasution, Irwan Padli (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
Google Drive is a cloud storage service that allows users to store various types of information, including images, videos, documents, spreadsheets and presentations. Google, Inc. has controlled Google Drive since April 2012. Users are provided with 15 GB of free storage space, which is backed by Google Docs. Google Drive provides convenient access 24/7 from any device. Users can choose to display files as a list of images or as a grid of large icons. While the grid view shows a preview of the first page of a file, the list view shows details about the owner of the file and the last modified date. Using the Share button, which gives access to document and editing settings, makes it easy to share files or documents. The service includes unlimited storage, advanced file filtering and reporting tools, eDiscovery services, comprehensive administration tools, and new APIs built with enterprise needs in mind.